The Impact of a 3D Visual Programming Tool on Students' Performance and Attitude in Computer Programming: A Case Study in Jordan - Al-Tahat, Khalid (Journal of cases on information technology, 2019)
Learning programming can be challenging, particularly object-oriented programming (OOP). However, using visualization could be useful in enhancing students' learning OOP concepts. In this study, the impact of using a 3D visual programming tool – Alice 2 – on student performance and attitude was explored in an introductory computer programming course using Java. Research participants were undergraduate computing students at Arab Open University – Jordan branch. Quasi-experimental design was adopted in this research, where two groups of students were chosen. The findings of this research showed that using Alice has positively impacted on students' performance and attitude towards computer programming and learning OOP concepts. The study suggests the incorporation of Alice in teaching introductory programming courses.